Computational Simulation of the Bioactivity of Selected Compounds Derived From the Sapium and Salvias Genera as Anticancer Agents. - Ouma, Russell B. O.; Raza, Usama; Ngari, Silas M.; Kibet, Joshua K.; Nisar, Uzair; Ali, Muhammad Waqar; Banerjee, Baisakhi (BioMed Research International, 2026)
The investigation into the anticancer properties of plant extracts, which are known to be effective therapeutic agents with minimal side effects, is gaining significant traction. The current study examined the bioactive compounds extracted from Sapium ellipticum and Salvia miltiorrhiza Bunge. Salvianolic acid (Sal B), ellagic acid (EA), [20‐3H]‐12‐deoxyphorbol‐13‐isobutyrate ([3H] DPB), and [20‐3H] phorbol‐12, 13‐dibutyrate ([3H] PDBu) have all been analyzed in vitro and in silico. Based on the molecular docking simulations, Sal B targeted DNA lyase, topoisomerase II alpha, and mTOR, with docking scores of −9.5, −6.9, and −7.9 kcal/mol, respectively. The docking scores of these compounds were comparable with those of EA, which had a docking score of −8.7, −6.5, and −7.6 kcal/mol when targeting DNA lyase, topoisomerase II alpha, and mTOR, respectively. Remarkably, Sal B (−9.0 kcal/mol), EA (−7.6 kcal/mol), [3H] PDBu (−8.7 kcal/mol), and [3H] DPB (−7.1 kcal/mol) showed weaker binding affinities to the mTOR kinase enzyme compared with rapamycin (−11.2 kcal/mol). With an IC50 of 11.6 μM, Sal B demonstrated remarkable efficacy and was almost as effective as the common inhibitor rapamycin (IC50 of 5.2 μM). With an IC50 of 21.9 μM, EA demonstrated a mild but similar inhibition. The assay and docking results were validated by the root mean square deviation (RMSD) plots of Sal B and EA, which demonstrated that they are both kinetically stable. The results of this study present a promising pathway for the advancement of therapeutic agents targeting breast cancer (BC) and prostate cancer (PCa). Eventually, these bioactive compounds will require precise clinical studies and in vivo testing to confirm their possible preventive and curative action.